Meal Frequency Does Not Affect Weight Loss in Overweight/Obese Women but Affects the Body Composition: A Randomized Controlled Trial - Koroglu, Yazgi Otuken; Ozturk, Mujgan (Routledge Journals, Taylor & Francis Ltd, 2024)
Objectives: Studies showing the relationship between meal frequency, weight loss and anthropometric measurements are contradictory. This study aims to determine the effect of meal frequency on weight loss, anthropometric measurements, and body composition. Methods: This is a parallel designed randomized control trial that was conducted with 40 female volunteers between the ages of 19-64 years, with a Body Mass Index (BMI) >= 27 who applied to a private clinic. Participants were randomized in two treatment arms (3 meals + 3 snacks/day (n = 20) vs 3 meals/day (n = 20)) and same dietary energy restriction (-500kcal) was applied for 3 months. Food consumption was questioned with 3 day food records, and anthropometric measurements and body composition were measured before the study and repeated each week till the end of the study by the researcher. Results: All of the participants completed the study period. Body weight (kg), BMI (kg/m(2)), total body fat (kg), body fat percentage (%), fat free mass (kg) and waist circumference (cm) decreased, while fat free mass percentage (%) increased significantly in both of the groups at the end of the study (p < 0.05). The rate of difference for body weight, BMI (kg/m(2)) and waist circumference (cm) were similar among the groups. When difference in body composition analyses was examined, the rate of reduction in total body fat (-18.82 +/- 4.97% vs -14.87 +/- 7.44%) and body fat percentage (%)(-10.79 +/- 4.63% vs -7.68 +/- 7.04%) and the rate of increase in fat free mass percentage (%)(7.65 +/- 3.16% vs 5.04 +/- 3.44%) were significantly higher in 3 meals + 3 snacks group (p < 0.05). Conclusion: When energy restricted and balanced weight loss programs are applied, alteration in body weight, BMI and waist circumference is not affected from meal frequency, but body composition does.
Keywords: Meal frequency; obesity; BMI; waist circumference; body composition